Fishery assessment of commercial three-year-olds of Halych carp - Грициняк, І. І.; Гурбик, В. В. (Scientific Progress & Innovations, 2017)
The basic fish-farming characteristics of three-year-old Halych carp, obtained in conditions of staple cultivation, are determined. The ecological conditions during growing trilogy of the Halych carp were within the fishery requirements. At the end of the growing season, the trunks were characterized by a high individual weight. The yield of fish feeding stood from 96 % to 98 %. The fish productivity index exceeded 2,000 kg/ha. The intensive increase in the weight of the body of fish and plant material in 2015 was recorded during the second decade of July, during this period, their absolute weight gain exceeded that in 2016 by almost 200 g. The main peak of the weight increase of fish in 2016 was observed in early July. The smallest weights of growth during the experimental period are noted in May. In 2015, the downward trend is also observed in early July. According to the indicator of specific growth rate, the peak of its growth was set in the second decade of July. Minimum growth rates in 2015 are fixed at the beginning of June. In order to characterize the economic quality of the Galician carp, an assessment of exterior characteristics during the growing season was conducted. Three-year-olds are characterized by high growth rates, have a small head and a fleshy structure. The three-year-olds of Halych carp, obtained in the Precarpathian pond conditions, are characterized by high economic indicators both in terms of the individual weight of fish, and in the overall fish productivity. Halych carp is a highly productive and promising object for further restoration of the aboriginal composition of cultivated fish species in the Precarpathian fish farm.